Efficiency of isotonic drinks for rehydration of athletes of children and youth age - R. A. Khanferyan; I. V. Radysh; V. N. Vybornov; Z. G. Ordzhonikidze; V. I. Pavlov; M. M. Korosteleva; A. A. Antonov (National Electronic Information Consortium (NEICON), 2022)
TThe most important factor limiting sports performance is insufficient fluid intake by athletes and dehydration of the body, while a significant decrease in performance and sports endurance begins with a dehydration level of 2 % and above.Objective: to study the effectiveness and safety of rehydration of the body of athletesskiers of children and youth using isotonic drinks «Izonok» and «Izonok+».Materials and methods: the main group (n = 12, 16.2 ± 1.4 years) took isotonic drinks for 30 days to compensate for fluid losses, the comparison group (n = 8, 15.7 ± 1.1 years) - drinking water. Bioimpedance body composition analysis was carried out on a KM-AR-01-"Diamant" device (RF, St.Petersburg), and central hemodynamic analysis was carried out on a «SIMONA 111» (LLC "Okulyus 2000", RF). The content of secretory immunoglobulin A (sIgA) and lysozyme in saliva samples of athletes was carried out by the enzyme immunoassay on an ANTHOS 2010 analyzer (Austria). Statistical data processing was carried out using the Statistica 6.0 software package from Stat Soft @ Ink USA.Results: The intake of an isotonic drink is accompanied by the stimulation of the production of secretory immunoglobulin (sIgA) and lysozyme compared to the consumption of drinking water. The total volume of fluid and the volume of extracellular fluid tended to increase; the volume of intracellular fluid remained practically unchanged; the amount of total water when taking isotonic increased.Conclusion: The investigated isotonic drinks "Izonok" and "Izonok+" are effective sports drinks for maintaining optimal water-salt balance and local immunity